When Do Firms Crack Under Pressure? Legal Professionals, Negative Role Models, and Organizational Misconduct - Gonsalves, Leroy (Organization Science, 2023)
Strain theory has long been invoked to explain organizational misconduct, with underperformance creating pressure for firms to engage in morally objectionable activities. In this paper, I examine whether underperformance increases the risk of organizational misconduct. Drawing on institutional arguments about professions and social learning, I further predict that when experiencing performance strain, legal professionals will push the boundaries of the law, increasing the risk of misconduct if they have influence over decision making. However, industry peers caught engaging in misconduct should serve as negative role models, reducing the risk of the firm resorting to misconduct to overcome performance shortfalls. I test and find support for these predictions using longitudinal data on material legal claims filed against S&P 1500 firms between 2000 and 2017. The study extends the strain theory of organizational misconduct, identifying how legal professionals and negative role models shape firms’ strategic responses to performance pressure.